The Life-Course Theory of Serial Killing: A Motivation Model - Deepak, S. A. (International journal of offender therapy and comparative criminology, 2021)
Case studies were conducted on eight serial killers in India who were inmates in central prisons of Kerala and Tamil Nadu. The study is a pioneering one on serial killers in the locale of the study. All available information about the lives of offenders were collected through multiple sources, including in-depth interviews with serial killers in the prisons, interviews of relatives of the killers, surviving victims, Investigators, crime scene studies, etc. The collected data have been chronologically arranged to construct biographies of the offenders. The rich biographies were carefully analyzed to construct an inclusive motivation model that can explain the process of individuals evolving into serial killers from a life-course approach. The motivation in each of the eight cases was explained with the proposed motivation model. The constructed motivation model is unique from the existing models, which were mostly rigid and, therefore, not applicable to cases outside the studies. The model proposes three critical determinants for explaining the evolution of a person into a serial killer, “nature,” “Deep Resting Life Factor,” and “key Incidents.” The study found a relatively short incident named “trigger” in the lives of six serial killers, which played a significant role in bringing out the dormant killer instinct and push the subjects toward the first murder. The comparative analysis of the motivation in different cases revealed that though there were recurring factors in the lives of serial killers, their interactions were more important than standalone factors. The study also found that there are no predetermined recipes for the making of a killer like some past researchers claimed.